The Dynamics of Social Conflict in Urban Communities: A Case Study on the Phenomenon of Gentrification in Jakarta - Ningsih, Widia (Journal Of Social Science (JoSS), 2025)
Urban transformation in Jakarta has accelerated rapidly over the past decade, driven by large-scale infrastructure development and increasing investment in real estate. While these changes have modernized the cityscape, they have also sparked complex social conflicts, particularly in areas undergoing gentrification. This study investigates the dynamics of social conflict arising in urban communities affected by gentrification in Jakarta. The objective is to analyze how spatial displacement, socioeconomic inequality, and contested urban identities contribute to tensions between long-term residents, new urban elites, and state or private developers. Using a qualitative case study approach, this research draws on in-depth interviews, participatory observation, and document analysis conducted in selected gentrifying neighborhoods such as Kampung Bayam and Jatinegara. The findings reveal that gentrification is not merely a physical transformation but a process marked by unequal power relations, loss of communal identity, and grassroots resistance. Social conflicts are triggered by opaque urban planning policies, forced evictions, and the erosion of traditional livelihoods. This study contributes to the growing discourse on urban justice and provides critical insights into how gentrification processes in the Global South manifest unique patterns of conflict and resilience. The research highlights the need for inclusive urban governance that balances development with the rights of existing communities.